1998
DOI: 10.1073/pnas.95.12.7024
|View full text |Cite
|
Sign up to set email alerts
|

The drug efflux protein, P-glycoprotein, additionally protects drug-resistant tumor cells from multiple forms of caspase-dependent apoptosis

Abstract: Multidrug resistance mediated by the drug eff lux protein, P-glycoprotein (P-gp), is one mechanism that tumor cells use to escape death induced by chemotherapeutic agents. However, the mechanism by which P-gp confers resistance to a large variety of structurally diverse molecules has remained elusive. In this study, classical multidrug resistant human CEM and K562 tumor cell lines expressing high levels of P-gp were less sensitive to multiple forms of caspasedependent cell death, including that mediated by cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
233
2
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(249 citation statements)
references
References 48 publications
11
233
2
3
Order By: Relevance
“…CEM GFP ± P-gp WT , CEM GFP -P-gp MUT , and CEM GFP cells were labeled with 51 Cr and then cultured with APO-1-1 anti-Fas antibody and cross-linked with protein A for 0 ± 6 h. CEM GFP ± P-gp MUT , and CEM GFP cells displayed significant cell death after 6 h incubation with APO-1-1 ( Figure 2A). By contrast and consistent with our previous studies using drug-selected P-gp expressing cells, 9 cell death induced by Fas antibodies in CEM GFP ± P-gp WT cells was significantly attenuated over both a dose and time range of APO-1-1 (Figure 2A, B). Taken together, these results suggested that Pgp ATPase and/or efflux function was necessary to confer resistance to Fas-induced cell death.…”
Section: Resultscontrasting
confidence: 52%
“…CEM GFP ± P-gp WT , CEM GFP -P-gp MUT , and CEM GFP cells were labeled with 51 Cr and then cultured with APO-1-1 anti-Fas antibody and cross-linked with protein A for 0 ± 6 h. CEM GFP ± P-gp MUT , and CEM GFP cells displayed significant cell death after 6 h incubation with APO-1-1 ( Figure 2A). By contrast and consistent with our previous studies using drug-selected P-gp expressing cells, 9 cell death induced by Fas antibodies in CEM GFP ± P-gp WT cells was significantly attenuated over both a dose and time range of APO-1-1 (Figure 2A, B). Taken together, these results suggested that Pgp ATPase and/or efflux function was necessary to confer resistance to Fas-induced cell death.…”
Section: Resultscontrasting
confidence: 52%
“…31 Therefore, in addition to drug transport function, P-gp may confer cell resistance by regulating some caspase-dependent apoptotic pathways. 32 Moreover, recent studies substantiated that soluble factors (cytokines, hormones, growth factors) or cell interaction with extracellular matrix (ECM) present in the tumor's microenvironment are determining factors in cancer cell survival and the emergence of drug resistance. 33,34 In particular, the BM microenvironment is likely to promote tumor cell survival by conferring protection from cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance (MDR) is a fatal event encountered during cancer chemotherapy (Chen et al, 1986;Gros et al, 1986a, b;Cole et al, 1992;Robinson et al, 1997;Smyth et al, 1998;Johnstone et al, 1999). To understand better MDR development, we employed the methylation sensitive-representational difference analysis technique (Yuan et al, 1999;Shan et al, 2000Shan et al, , 2002a to study DNA hypermethylation events in a human MDR breast cancer cell line, MCF7/AdrR, as compared to its parental line, MCF7/WT.…”
mentioning
confidence: 99%